The Influence Of Big Five Personality Traits On Online Impulse Buying Behavior Of Shopee Medan Customers: Pengaruh Big Five Personality Traits Terhadap Perilaku Pembelian Impuls Online Pada Pelanggan Shopee Medan - Vanessa; Eddy (Universitas Muhammadiyah Palu, 2025)
The rapid growth of the internet has altered shopping behaviors, increasing online impulse buying behavior. However, Shopee experienced a decrease in the number of website visits, signifying a decline in consumer engagement. Therefore, the writer researches to study the Big Five Personality Traits as factors that might influence online impulse buying behavior. The Big Five Personality Traits, comprising openness to experience, conscientiousness, extraversion, agreeableness, and neuroticism are closely linked to customer interactions with online platforms, spontaneous buying decisions, and impulsive purchase, depending on personal characteristics and emotional states. The study employed the IBM SPSS V.30 for quantitative research. Both descriptive and causal approach were used. The research was conducted on a sample of 100 individuals utilizing convenience sampling. This study passed the validity, reliability, normality, multicollinearity, heteroscedasticity and multiple linear regression test, resulting in the regression equation ? = 2.562 + 0.090?1 + 0.135?2 + 0.165?3 + 0.101?4 + 0.134?5. Based on the hypothesis testing results, the Big Five Personality traits influence online impulse buying behavior of Shopee Medan customers, either partially or simultaneously. Additionally, the Big Five Personality traits influence 72.4% of online impulse buying behavior. The writer suggests Shopee to include elements that encourage creativity and idea cultivation, provide clearer guidance and decision-making tools, improve feedback features, incorporate more prominent and accessible social responsibility features, and improve customer assistance.